Effects of the hypocholesteremic agent trifluperidol on the sterol, steryl ester, and fatty acid metabolism of Saccharomyces cerevisiae. - Sobus, M T (1977)
Trifluperidol (TFP), at a concentration of 100 muM, inhibited the 24-h growth of Saccharomyces cerevisiae by about 30%. Effects on lipid metabolism were investigated by monitoring the incorporation of [1-14C]sodium acetate into various lipid fractions after 4 and 24 h of growth in the presence of several concentrations of TFP. Although little effect was noted on the amount of free sterols, 24-h incorporation of label into steryl esters was increased two- to fourfold by 100 muM TFP. Major sterol components of the steryl ester fraction isolated from an untreated culture were zymosterol (48%) and ergosterol (24%), whereas from the TFP-treated culture delta8,24(28)-ergostadienol (66.6%) and delta8-ergostenol (14.7%) were most abundant. Free sterols present in the highest concentration in the untreated culture were ergosterol (78.2%) and lanosterol (13%); whereas delta8,22-ergostadienol (38.5%), delta8-ergostenol (35.4%), and delta8,24(28)-ergostadienol (25.4%) were the most abundant free sterols obtained from the TFP-treated culture. Thus, the major block in the sterol biosynthetic pathway in yeast appears to be delta8 leads to delta7 isomerization. In these same cultures the relative amounts of C12 and C14 acids isolated from both steryl ester and miscellaneous lipid fractions were increased more than threefold over controls.